Analysis of Food Security Level of Urban and Rural Households in East Java Province - Puryantoro, Puryantoro; Hasbiadi, Hasbiadi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2021)
Food security is an issue that continues to roll because it is closely related to people's welfare. Not only urban but rural residents have also been targeted in various strategies to meet pagan needs. This study aimed to analyze household food security in both urban and rural areas in East Java. Data collection uses Susenas secondary data for 2016-2019 issued by BPS East Java. The share of food expenditure analyzes the data. The analysis results show that the population in East Java, both in urban and rural areas, is at the level of food security status because the share value of food expenditure is less than 60%. The share of urban food expenditure is lower than the share of rural food expenditure.